EFFICIENCY OF USE OF INVENTORIES IN TRADE ENTERPRISE - Кулік, Анна; Самойленко, Антоніна (SWorldJournal, 2024)
The article discusses methodical approaches to the creation of inventory in a trading company. Stocks are the most important component of competitiveness and are found at all stages of goods movement. The need for commodity stocks requires the creation of